2019
DOI: 10.1158/1535-7163.mct-18-0824
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Modified Antisense Oligonucleotide Against ARL4C Inhibits Primary and Metastatic Liver Tumor Growth

Abstract: ADP-ribosylation factor-like 4c (ARL4C) is identified as a small GTP-binding protein, which is expressed by Wnt and EGF signaling and plays an important role in tubulogenesis of cultured cells and the ureters. ARL4C is little expressed in adult tissues, but it is highly expressed in lung cancer and colorectal cancer and shown to represent a molecular target for cancer therapy based on siRNA experiments. This study revealed that ARL4C is highly expressed in primary hepatocellular carcinoma (HCC) tumors and colo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 32 publications
2
48
0
Order By: Relevance
“…When the relationship between IHC staining of ARL4C and prognosis in surgically resected lung cancer patients was evaluated, ARL4C expression in lung adenocarcinoma was inversely correlated with relapse‐free survival. These results are consistent with the analyzed data from GSE datasets of lung cancer and our previous reports on liver cancers and liver tumors that metastasize from colon cancer . Furthermore, multivariate analysis using clinical data in this study identified high ARL4C expression as an independent prognostic factor in relapse‐free survival.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…When the relationship between IHC staining of ARL4C and prognosis in surgically resected lung cancer patients was evaluated, ARL4C expression in lung adenocarcinoma was inversely correlated with relapse‐free survival. These results are consistent with the analyzed data from GSE datasets of lung cancer and our previous reports on liver cancers and liver tumors that metastasize from colon cancer . Furthermore, multivariate analysis using clinical data in this study identified high ARL4C expression as an independent prognostic factor in relapse‐free survival.…”
Section: Discussionsupporting
confidence: 92%
“…ARL4C represents a molecular target for the treatment of lung, colon and liver cancers, and ARL4C ASO‐1316 is effective in primary and metastatic liver tumors expressing ARL4C . Whether ARL4C ASO‐1316 affects proliferation and migration of lung cancer cells harboring KRAS or EGFR mutations was examined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations